Native Languages of the Northwest Coast (Oregon Historical Society, 1985)
Map of distribution of indigenous peoples of the nothwestern coast of North America. Map is oriented according to up-river (top of map) and down-river (bottom of map) in keeping with way that the indigenous groups represented on the map represent geographic orientation in their cultures. COAST-4 is a letter that accompanied this map explaining the reasoning behind this. The collection holds three versions of this map; this is the latest version.